2022
DOI: 10.1108/aeat-09-2021-0291
|View full text |Cite
|
Sign up to set email alerts
|

Vibration response analysis and hoop layout optimization of spatial pipeline under random excitation

Abstract: Purpose In many cases, the external pipelines of aero-engine are subjected to random excitation. The purpose of this paper is to reduce the vibration response of the pipeline system effectively by adjusting the hoop layout. Design/methodology/approach In this paper, a spatial pipeline supported by multi-hoops is taken as the object, the methods of solution of the vibration response of the pipeline system by using pseudo excitation and hoop layouts optimization with amplitude reduction of vibration response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The results showed that the vibration of the pipeline can be effectively suppressed by adding a sleeve in the branch pipe, and the vibration amplitude of the optimized pipeline structure is 98% lower than that of the original structure. Wang et al (2022) proposed an optimization method of clamp arrangement aiming at vibration reduction by considering the space pipeline with multi-stirrup support of aeroengine as the research object. The results indicated that the maximum vibration response of the optimised pipeline system under random excitation decreases by 32.8%.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the vibration of the pipeline can be effectively suppressed by adding a sleeve in the branch pipe, and the vibration amplitude of the optimized pipeline structure is 98% lower than that of the original structure. Wang et al (2022) proposed an optimization method of clamp arrangement aiming at vibration reduction by considering the space pipeline with multi-stirrup support of aeroengine as the research object. The results indicated that the maximum vibration response of the optimised pipeline system under random excitation decreases by 32.8%.…”
Section: Introductionmentioning
confidence: 99%